2008
DOI: 10.1055/s-0028-1086055
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome of Endonasal Endoscopic Skull Base Reconstruction with Nasal Turbinate Graft

Abstract: Objective: To study the long-term outcome of endonasal endoscopic skull base reconstruction with nasal turbinate tissue free graft. Patients and Methods: This study included 55 consecutive patients who underwent endonasal endoscopic skull base reconstruction with nasal turbinate graft and were available for follow-up. They were 30 patients with pituitary adenomas, 20 with cerebrospinal fluid (CSF) rhinorrhea of different etiologies, three with meningoencephalocele, and two with skull base meningiomas. Autologo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…In subsequent meta-analyses of surgically created defects, 6,7 areas of high-flow (i.e., high CSF pressure) were at risk of failure with free grafts and appeared to benefit from vascularized tissue grafts. El-Banhawy et al 12 determined that the size of the bony defect determined the dural pulsation and prolapse at the site of the duraplasty, implying that a rigid underlay may mitigate pulsations from the intracranial compartment as a graft attempts to adhere to the skull base. It is arguable if bony or rigid repair of the defect is required at all, however.…”
Section: Discussionmentioning
confidence: 99%
“…In subsequent meta-analyses of surgically created defects, 6,7 areas of high-flow (i.e., high CSF pressure) were at risk of failure with free grafts and appeared to benefit from vascularized tissue grafts. El-Banhawy et al 12 determined that the size of the bony defect determined the dural pulsation and prolapse at the site of the duraplasty, implying that a rigid underlay may mitigate pulsations from the intracranial compartment as a graft attempts to adhere to the skull base. It is arguable if bony or rigid repair of the defect is required at all, however.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that an inferiorly based middle turbinate mucosal graft can be rotated widely and serve as reconstruction material for surgical defects after sellar, transtuberculum/transplanum, or unilateral transcribiform approaches, as well as treatment of post‐traumatic and spontaneous CSF leaks 16, 23. The use of middle turbinate mucosa as a free graft has also been successfully reported for managing CSF leaks and to reconstruct skull base defects created by minimally invasive pituitary surgery and to repair CSF rhinorrhea, meningoceles, and meningiomas 26–29. The middle turbinate nasal mucosa graft has been shown to be reliable and cost efficient 28.…”
Section: Discussionmentioning
confidence: 99%
“…Animal models have shown that integration of fascial dural repair may take place as soon as one week postoperatively, with a durable fibrous ingrowth as soon as two weeks [18]. This healing process, however, depends greatly on the size of the skull base defect, the nature of the material used for repair, and history of radiation treatment [19]. …”
Section: Discussionmentioning
confidence: 99%